5x-4=3x+2x+3-2+1

Simple and best practice solution for 5x-4=3x+2x+3-2+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-4=3x+2x+3-2+1 equation:


Simplifying
5x + -4 = 3x + 2x + 3 + -2 + 1

Reorder the terms:
-4 + 5x = 3x + 2x + 3 + -2 + 1

Reorder the terms:
-4 + 5x = 3 + -2 + 1 + 3x + 2x

Combine like terms: 3 + -2 = 1
-4 + 5x = 1 + 1 + 3x + 2x

Combine like terms: 1 + 1 = 2
-4 + 5x = 2 + 3x + 2x

Combine like terms: 3x + 2x = 5x
-4 + 5x = 2 + 5x

Add '-5x' to each side of the equation.
-4 + 5x + -5x = 2 + 5x + -5x

Combine like terms: 5x + -5x = 0
-4 + 0 = 2 + 5x + -5x
-4 = 2 + 5x + -5x

Combine like terms: 5x + -5x = 0
-4 = 2 + 0
-4 = 2

Solving
-4 = 2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 72=5c+7c-2c | | n+5=-1-16 | | 2(-3a+5)=2y+3 | | 68=4v | | a(a^7+1)-7(a^7+1)=0 | | 4x-3=x-3+3x | | 3(4)-6+4+8=42 | | m+5=1 | | 12x-7=27x+3 | | -1x=13 | | 34a-4(5d+2)=36 | | 235=177-x | | -5n-15n=10 | | 6x-2=4x-(-2x+2) | | J=9(3.14)p | | 3x-3=2x-16 | | -5n-n=10 | | 3x-2=16-x^2 | | 185-u=252 | | 3x+5+6x=15 | | 14x+7-2=7 | | 11(y-2)=13(y+4) | | 3p^2+4p=8 | | 11T=8D+12pm | | 4(x+2)+3(2x-5)=31 | | (4x-25)+(3x-75)=180 | | 3-k=14 | | 6(4)+-25=7+-2(4) | | (8x+25)+(3x+75)=180 | | (2x-7)-(x-6)=14 | | 3x-3-24=4x-4 | | 2x-11=3x-7 |

Equations solver categories